Stillbirth after COVID-19 in Unvaccinated Mothers Can Result from SARS-CoV-2 Placentitis, Placental Insufficiency, and Hypoxic Ischemic Fetal Demise, Not Direct Fetal Infection: Potential Role of Maternal Vaccination in Pregnancy - David A. Schwartz (Viruses, 2022)
Stillbirth is a recently recognized complication of COVID-19 in pregnant women. Other congenitally transmitted infections from viruses, bacteria and parasites can cause stillbirth by infecting fetal organs following transplacental transmission of the agent from the maternal bloodstream. However, recent research on pregnant women with COVID-19 having stillbirths indicates that there is another mechanism of stillbirth that can occur in placentas infected with SARS-CoV-2. In these cases, viral infection of the placenta results in SARS-CoV-2 placentitis, a combination of concurrent destructive findings that include increased fibrin deposition which typically reaches the level of massive perivillous fibrin deposition, chronic histiocytic intervillositis and trophoblast necrosis. These three pathological lesions, in some cases together with placental hemorrhage, thrombohematomas and villitis, result in severe and diffuse placental parenchymal destruction. This pathology can involve greater than one-half of the placental volume, averaging 77% in the largest study of 68 cases, effectively rendering the placenta incapable of performing its function of oxygenating the fetus. This destructive placental process can lead to stillbirth and neonatal death via malperfusion and placental insufficiency which is independent of fetal infection. Fetal autopsies show no evidence that direct infection of fetal organs is contributory. Because all mothers examined have been unvaccinated, maternal vaccination may prevent viremia and consequent placental infection.